Optical fiber amplifier (EDFA) for wavelength-division multiplexing systems - Guo, Xin. (2008)
In this thesis, based on the study of various gain-flattening and gain-control techniques, the author has proposed and demonstated a new configuration of gain-equalized EDFA for WDM systems by using short-period fiber Bragg grating (FBGs).